Commercialisation of microgrinding wheels. (3rd November 2008) - Jackson, Mark J.; Robinson, Grant M.
This paper describes the development and commercialisation of laser dressed grinding wheels with faceted morphology. The approach used in this paper is based on surface melting of a vitrified grinding wheel and measuring features such as grain size, cooling rate and melt depth as a function of laser fluence. The findings of this course of research lead the authors to believe that a specific morphology is dependent upon cooling rate and laser fluence. The findings show how certain morphologies form as a function of cooling rate and laser fluence. The results imply that laser dressed grinding wheels can be used for machining different materials at different speeds. This paper also discusses how the micro grinding tools produced can be commercialised. The originality in this paper is focused on the formation on minute cutting points using increasing laser fluences.